2020
DOI: 10.48550/arxiv.2005.11109
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On the Distance of SGR 1935+2154 Associated with FRB 200428 and Hosted in SNR G57.2+0.8

S. Q. Zhong,
Z. G. Dai,
H. M. Zhang
et al.

Abstract: Owing to the detection of an extremely bright fast radio burst (FRB) 200428 associated with a hard X-ray counterpart from the magnetar soft gamma-ray repeater (SGR) 1935+2154, the distance of SGR 1935+2154 potentially hosted in the supernova remnant (SNR) G57.2+0.8 can be revisited. Under the assumption that the SGR and the SNR are physically related, in this Letter, by investigating the dispersion measure (DM) of the FRB contributed by the foreground medium of our Galaxy and the local environments and combini… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…This non-detection, together with the relatively low inferred extinction towards the source at NIR wavelengths (A J ≈ 2.0 ± 0.3 mag) allows us to place the most stringent extinction-corrected constraints till date on second-timescale flares from the source of ≈ 85 − 150 Jy ms at optical/NIR wavelengths (ν ∼ 10 14 Hz). The NIR limit corresponds to an energy E 3 × 10 36 erg at a distance of 9 kpc (Zhong et al 2020), and is within an order of magnitude of that reported in the radio for FRB 200428 at 1.25 GHz (≈ 2 × 10 35 erg; Bochenek et al 2020). It is also several orders of magnitude deeper than reported optical limits from nearby well-localized FRBs (∼ 10 43−46 erg; Hardy et al 2017;Andreoni et al 2020).…”
Section: Discussionsupporting
confidence: 76%
“…This non-detection, together with the relatively low inferred extinction towards the source at NIR wavelengths (A J ≈ 2.0 ± 0.3 mag) allows us to place the most stringent extinction-corrected constraints till date on second-timescale flares from the source of ≈ 85 − 150 Jy ms at optical/NIR wavelengths (ν ∼ 10 14 Hz). The NIR limit corresponds to an energy E 3 × 10 36 erg at a distance of 9 kpc (Zhong et al 2020), and is within an order of magnitude of that reported in the radio for FRB 200428 at 1.25 GHz (≈ 2 × 10 35 erg; Bochenek et al 2020). It is also several orders of magnitude deeper than reported optical limits from nearby well-localized FRBs (∼ 10 43−46 erg; Hardy et al 2017;Andreoni et al 2020).…”
Section: Discussionsupporting
confidence: 76%
“…Identification of FRB with rotating neutron stars predicts that FRB activity should be modulated, at some level, at the rotation rate. Periodicity has not been observed in FRB 121102, the only FRB for which abundant data exist (Zhang et al 2018); see discussion in Katz (2019). If "cosmological" and Galactic FRB are qualitatively similar phenomena, periodicity should be detectable in any FRB that repeats frequently.…”
Section: Discussionmentioning
confidence: 99%
“…A past argument (Katz 2020) against a neutron star origin of FRB was the absence of periodicity in repeating FRB, particularly in the well-studied FRB 121102 (Zhang et al 2018). SGR 1935+2154 has a period of 3.245 s (Israel et al 2016), which would be expected to modulate the observable activity of FRB 200428, whatever its mechanism of emission, unless its magnetic field be a dipole aligned with the spin axis.…”
Section: Frbmentioning
confidence: 99%
“…SGR 1935+2154 is a magnetar with rotational period P = 3.24 s (Stamatikos et al 2014), a surface dipolar magnetic field B NS 2.2 × 10 14 G derived from the spin-down rate Ṗ 1.43 × 10 −11 s s −1 (Israel et al 2016). It is associated with supernova remnant (SNR) G57.2+0.8 (Gaensler 2014), of which the distance is roughly within a range of 6-15 kpc (Sun et al 2011;Pavlović et al 2013;Kothes et al 2018;Zhong et al 2020;Zhou et al 2020). In this work, we adopt D L = 10 kpc for SGR 1935+2154, and the uncertainty of D L will not affect our results significantly.…”
Section: Magnetar-asteroid Interactionmentioning
confidence: 99%